Applied Aspect of Saliva in Orthodontics - Snigdha Pattanaik (Indian Journal of Forensic Medicine & Toxicology, 2020)
Saliva influences oral health both through its non-specific physicochemical properties, as well as throughmore specific effects. The proline-rich proteins, statherin and the histatins are salivary proteins that influencecalcium phosphate chemistry, initial plaque formation and candida infection. Increases or decreases inmastication may affect saliva output. Fixed orthodontic appliances introduce an additional constituent to theoral cavity complex that may enhance the environment in a variety of ways. On the other hand, Orthodontictreatment leads to changes in the oral environmental factors that encourage changes in salivary flow rate,viscosity, pH, bacterial count, increased plaque index, and other more things which all are factors supplementthe risk of caries activity and shake the stability of the oral environment. This manuscript highlights theeffect of saliva on orthodontic treatment.